Development of Artificial Intelligence–Assisted Whole Number Mathematics Teaching Materials Integrating Plug and Unplug Activities to Enhance Fifth-Grade Students’ Critical Thinking Skills - Yeni Kartika Dewi; Punaji Setyosari; Intan Sari Rufiana (Papanda Publisher, 2026)
This study aimed to develop Artificial Intelligence (AI)–assisted mathematics teaching materials integrating plug and unplug activities on the topic of whole numbers (0–100,000) for fifth-grade elementary school students. The research employed a research and development (R&D) approach using a systematic instructional design model. The developed product combined digital plug-based activities using a Scratch application with simple AI features and unplug-based activities through concrete learning media. Data were collected through expert validation sheets, teacher and student practicality questionnaires, and pre-test and post-test instruments to measure effectiveness and students’ critical thinking skills. Data analysis was conducted using descriptive quantitative techniques. The results indicated that the teaching materials achieved a very high level of validity (89.13%), practicality (95.25%), and effectiveness (95.4%). In addition, students’ critical thinking skills reached a very high category, with an average achievement of 97.9%. These findings suggest that AI-assisted mathematics teaching materials integrating plug and unplug activities are feasible, practical, and effective in supporting critical thinking development among elementary school students. The study contributes to the integration of Artificial Intelligence, computational thinking, and student-centered learning in elementary mathematics education.